2010
DOI: 10.1111/j.1365-2230.2009.03465.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of skin carcinogenicity by alcohol and ultraviolet light

Abstract: In western societies, casual consumption of alcohol during such outdoor activities as barbecuing and sunbathing is common. The current literature shows that alcohol drinkers have increased episodes of sunburn and a higher prevalence of skin cancer. Moreover, recent evidence suggests that the combination of subcarcinogenic (minimal) ultraviolet (UV) exposure with other behavioural, environmental and xenobiotic factors has resulted in increased incidents of skin-related health problems that also result in skin-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 30 publications
1
59
0
1
Order By: Relevance
“…An increased risk of sunburn after alcohol uptake has already been established in previous studies [22]. Warthan et al [34] revealed that people consuming alcohol during time spent on the beach had a more severe sunburn than nondrinkers.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…An increased risk of sunburn after alcohol uptake has already been established in previous studies [22]. Warthan et al [34] revealed that people consuming alcohol during time spent on the beach had a more severe sunburn than nondrinkers.…”
Section: Discussionmentioning
confidence: 89%
“…Bearing in mind that the skin represents the barrier to the environment and is thus exposed to a multiplicity of harmful influencing factors, e.g., ultraviolet (UV) light [21], it could be of importance to determine if the natural defense system of the skin is compromised by alcohol consumption. Furthermore, in recent years, epidemiological data has demonstrated that alcohol consumption is indeed a risk factor for sunburn and associated with a risk of nonmelanoma skin cancer and melanoma [22]. …”
Section: Introductionmentioning
confidence: 99%
“…It is possible that previous skin cancer studies which did not adjust for alcohol consumption may have over-estimated the effect attributed to sun or solarium exposure. Alcohol may have carcinogenic effects through its conversion to acetaldehyde (18), which is a known carcinogen (29). Collectively, these results suggest that future epidemiological studies of UV exposure and skin cancer should adjust for alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity has been associated with history of sunburn (11,12) and current sunscreen use (13), but inversely with solarium use (14); tobacco smoking is associated inconsistently with sunscreen use (15,16) and with sunbed use (16,17); while consumption of alcohol occurs commonly during outdoor activities (18) and has been associated with the occurrence of sunburn (12,19).…”
Section: Introductionmentioning
confidence: 99%
“…Ela favorece o desenvolvimento de ambas as formas de câncer da pele: melanoma e não melanoma. O não melanoma está associado à ação solar cumulativa, e o melanoma, a episódios intensos de exposição solar aguda, que resulta em queimadura solar (Armmings et.al., 1997;Rigel, 2008;Saladi et al, 2009 (Harwood et al, 2000;Nindl et al, 2007 A desregulação desta homeostase pode perturbar o equilíbrio da unidade de melanina epidermal e desencadear a proliferação contínua dos melanócitos, o que pode levar ao desenvolvimento de um melanoma maligno (Haass et al, 2004).…”
Section: Amo Muito Vocêsunclassified